Improving the Precision of On-Wafer W-Band Scalar Load-Pull Measurements - Nicholas C. Miller; Michael Elliott; Eythan Lam; Ryan Gilbert; Jansen Uyeda; Robert L. Coffie (IEEE Journal of Microwaves, 2023)
This article presents an empirical investigation of calibration effects on load-pull measurements collected on wafer and at W-band frequencies. An analysis of scattering parameter (S-parameter) measurements provides insight into how small-signal metrics germane to load pull are affected by choice of the calibration technique. It is found that off-wafer line-reflect-reflect-match (LRRM) calibrated measurements of the same transistor with different probes exhibit drastically different maximum small-signal gains compared to equivalent on-wafer multiline thru-reflect-line (mTRL) calibrated measurements. Load-pull measurements are heavily influenced by choice of calibration algorithm, and LRRM calibrated large-signal measurements collected with different waveguide probes yield variations in large-signal gain of over 2 dB and variations in peak PAE of over 24 percentage points. The equivalent on-wafer mTRL calibrated load-pull measurements collected with different waveguide probes are consistent to within 0.1 dB for large-signal gain and 1 percentage point for peak PAE. This work provides quantitative evidence that on-wafer mTRL calibration with well-designed calibration structures is preferred for large-signal measurements collected at millimeter-wave frequencies. If utilization of on-wafer mTRL calibration is not possible, this work suggests using similar measurement setups, i.e., waveguide probes, calibration standards, etc., for evaluating on-wafer unmatched transistors in a consistent manner.